Impact of functional, communicative, critical and distributed health literacy on self-management behaviors in chronic disease patients across socioeconomic groups - Shichen Chen; Qin Bai; Jinghui Zhu; Guilin Liu (BMC Public Health)
Abstract Background Effective self-management behaviors offer a promising pathway to address the health challenges faced by patients with chronic diseases. As a key factor influencing self-management behaviors, multidimensional health literacy has yet to be systematically studied in relation to its impact on patients with chronic diseases across different socioeconomic statuses. Objective To systematically investigate the influence of functional, communicative, critical, and distributed health literacy on self-management behaviors among patients with chronic diseases from different socioeconomic statuses. Methods A modified multidimensional health literacy and self-management behavior questionnaire was used to assess the health literacy and self-management behaviors of patients with chronic diseases. A total of 590 valid samples were obtained, and participants were divided into high and low socioeconomic status groups based on their socioeconomic background. Correlation analysis and multiple linear regression were conducted to explore the influence of various dimensions of health literacy on self-management behaviors across different socioeconomic statuses. Results After controlling for confounding variables, the communicative (β = 0.262, P < 0.01) and distributed (β = 0.343, P < 0.01) health literacy dimensions showed a significant positive impact on self-management behaviors in the low socioeconomic status group. In the high socioeconomic status group, critical (β = 0.253, P < 0.05) and distributed (β = 0.267, P < 0.01) health literacy demonstrated a significant positive effect on self-management behaviors. No significant impact was observed for functional health literacy in either group. Conclusions The study comprehensively reveals the distinct effects of different dimensions of health literacy on self-management behaviors among patients with chronic diseases from varying socioeconomic statuses. These findings provide a theoretical basis for developing strategies aimed at improving self-management behaviors through health literacy enhancement, particularly tailored to patients from different socioeconomic backgrounds.